2015
DOI: 10.1089/acm.2014.0114
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aerobic Exercise Associated with Abdominal Microcurrent: A Preliminary Study

Abstract: Objective: To analyze the short-and long-term effects of microcurrent used with aerobic exercise on abdominal fat (visceral and subcutaneous).Methods: Forty-two female students from a university population were randomly assigned into five group: intervention group (IG) 1 (n=9), IG2 (n=9), IG3 (n=7), IG4 (n=8), and placebo group (PG) (n=9). An intervention program of 10 sessions encompassing microcurrent and aerobic exercise (performed with a cycloergometer) was applied in all groups, with slightly differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 45 publications
1
32
0
3
Order By: Relevance
“…However, in this study there was a significant loss of visceral fat in both intervention groups; nonetheless, the reduction was not greater in the microcurrent protocol when compared with only exercise protocol. Nevertheless, a study similar to the present, but in healthy subjects, found a significant reduction in visceral fat due to microcurrent [39]. One possible explanation would be the beta-blockers taken by the subjects, given that their mechanism of action is based on competition with endogenous catecholamines at the β-adrenergic receptor level [51], not allowing the activation of β-adrenergic by the effect of electrical current.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…However, in this study there was a significant loss of visceral fat in both intervention groups; nonetheless, the reduction was not greater in the microcurrent protocol when compared with only exercise protocol. Nevertheless, a study similar to the present, but in healthy subjects, found a significant reduction in visceral fat due to microcurrent [39]. One possible explanation would be the beta-blockers taken by the subjects, given that their mechanism of action is based on competition with endogenous catecholamines at the β-adrenergic receptor level [51], not allowing the activation of β-adrenergic by the effect of electrical current.…”
Section: Discussionsupporting
confidence: 62%
“…[38] electro-stimulation promotes changes in cells' structure and behavior, by acting on voltage-dependent potassium channels, and on norepinephrine levels. The increase of catecholamines seems to induce a membrane depolarization, which raises intracellular levels of cyclic adenosine monophosphate, boosting the activation of protein kinase A and lipolytic enzymes (hormone sensitive lipase and lipoprotein lipase) responsible for triglyceride degradation [13], [19], [20] and [39]. The decrease of subcutaneous abdominal fat could be an important achievement, as it increases the activation of deep subcutaneous adipocytes, which are larger in size and with high expression of pro-inflammatory, lipogenic and lipolytic genes and a high proportion of saturated FA, that can be compared to visceral fat in male [12].…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonography was performed using a ViamoTM 7 ultrasound system (Toshiba Medical Systems, Tustin, California) to measure subcutaneous and visceral abdominal fat below the xiphoid apophysis, and navel fat below the navel [16].…”
Section: Abdominal Fatmentioning
confidence: 99%
“…A 25 Hz frequency (impulse duration and resting duration of 20 ms) was used during the first 20 min, followed by another application of 20 min at 10 Hz frequency (impulse duration and resting duration of 50 ms). In the experimental group, the microcurrent's intensity was under each individual's sensitivity threshold (registered values were superior to 700 mA and inferior to 1000 mA) [16,28,29]. In the placebo group, all the procedures were similar to the EG but the microcuurent device was off.…”
Section: Microcurrent Protocolmentioning
confidence: 99%
See 1 more Smart Citation